Regulation of AURORA B function by mitotic checkpoint protein MAD2. Issue 16 (17th August 2016) - Shandilya, Jayasha; Medler, Kathryn F.; Roberts, Stefan G. E.
ABSTRACT: Cell cycle checkpoint signaling stringently regulates chromosome segregation during cell division. MAD2 is one of the key components of the spindle and mitotic checkpoint complex that regulates the fidelity of cell division along with MAD1, CDC20, BUBR1, BUB3 and MAD3. MAD2 ablation leads to erroneous attachment of kinetochore-spindle fibers and defective chromosome separation. A potential role for MAD2 in the regulation of events beyond the spindle and mitotic checkpoints is not clear. Together with active spindle assembly checkpoint signaling, AURORA B kinase activity is essential for chromosome condensation as cells enter mitosis. AURORA B phosphorylates histone H3 at serine 10 and serine 28 to facilitate the formation of condensed metaphase chromosomes. In the absence of functional AURORA B cells escape mitosis despite the presence of misaligned chromosomes. In this study we report that silencing of MAD2 results in a drastic reduction of metaphase-specific histone H3 phosphorylation at serine 10 and serine 28. We demonstrate that this is due to mislocalization of AURORA B in the absence of MAD2. Conversely, overexpression of MAD2 concentrated the localization of AURORA B at the metaphase plate and caused hyper-phosphorylation of histone H3. We find that MAD1 plays a minor role in influencing the MAD2-dependent regulation of AURORA B suggesting that the effects of MAD2 on AURORA B are independent of the spindle checkpoint complex. Our findings reveal that, in addition to its role in checkpoint signaling, MAD2 ensures chromosome stability through the regulation of AURORA B.